Evolution of ICT infrastructure in UiTM / Rozita Mengen and Jamaluddin Johan - Mengen, Rozita; Johan, Jamaluddin (2022)
The article is about the evolution of UiTM ICT infrastructure, in general. Objective of the article review is to inform and record the changing technology applied throughout the years. The information will circulate around topics on the growth of network communications services that supports UiTM applications over the years. Method of identifying data is based on information reviewed from the paper written by the first author and the work experiences from both authors in the field. Findings from the collection of data will be a general chronological evolution of the entire ICT infrastructure system in UiTM for both intranet and the Internet link. These explanation enables the understanding on how ICT infrastructure evolution and growth in UiTM and can be referred to as a guideline for current or future administrators.